Exposure of Magnificent Frigatebird (Fregata magnificens) and Brown Booby (Sula leucogaster) to Metals and Selenium in Rio de Janeiro State (Brazil) Coastal Waters - Padilha, Janeide de Assis; da Cunha, Larissa Schmauder Teixeira; de Castro, Rayane Moreira; Malm, Olaf; Dorneles, Paulo Renato (Orbital: The Electronic Journal of Chemistry, 2018)
This study used feathers of brown booby (Sula leucogaster) and magnificent frigatebird (Fregata magnificens) from Cagarras Archipelago, an area under strong anthropogenic influence, for evaluating the exposure of these seabirds to Cd, Sn, Mn, Cu and Se. Average concentrations (µg.Kg-1, dry weight) in feathers of brown booby were Cd 28.1, Sn 210.6, Cu 8233.4, Se 2343 and Mn 1635.7 and for frigatebird were Cd 82.9, Sn 319.6, Cu 8008.6, Se 3026 and Mn 5143. Regarding brown boobies, no significant difference was found between sexes or age (adults vs. juveniles) considering all measured elements. In addition, no significant correlation was observed between Sn, Cd and Cu concentrations and the following biometric parameters (BPs): body weight (BW) and tarsus (TrL), wing (WL), tail (TiL) and beak length (BL), for both species. However, significant negative correlations were observed between Se concentrations and TrL for magnificent frigatebird and brown booby. Concerning possible interspecific dissimilarities for juveniles, there was no significant difference for Sn, Se and Cd concentrations; however, significantly higher Cu and Mn concentrations were found in brown boobies. When adults were compared, significantly higher Cd and Mn concentrations were found in magnificent frigatebirds. These interspecific differences may occur due to dissimilarities in diet; however, the feeding habits of these seabirds around the study area are unknown. Additional studies on the diet of these species are necessary to shed further light on the interspecific differences verified. The concentrations found in the feathers of the seabirds in question do not denote a risk for the survival of the seabirds of the Cagarras Archipelago.DOI: http://dx.doi.org/10.17807/orbital.v10i2.1050